Predictive performance of triglyceride-glucose index on asymptomatic multiple organ damage in patients with newly diagnosed hypertension - Ahmet Kivrak; Alp Yildirim (Permanyer, 2023)
Background: Insulin resistance (IR) contributes to the development of hypertension and mediated organ damage (HMOD) through various mechanisms. Objectives: The objective of the study was to assess the diagnostic performance of the triglyceride- glucose (TyG) index, a surrogate marker of IR, in predicting the presence and severity of HMOD in newly diagnosed untreated hypertensive patients from an academic training and research hospital. Methods: The study included 438 patients with newly diagnosed, untreated hypertension. The control group comprised normotensive individuals matched on a 1:1 ratio based on age, gender, body mass index, and smoking using the nearest neighbor method. The presence of HMOD was defined by renal damage (microalbuminuria > 30 mg/day or proteinuria > 150 mg/day), vascular damage (carotid intima-media thickness > 0.9 mm or presence of plaque), or cardiac damage (left ventricular mass index > 95 g/m2 in women and > 115 g/m2 in men). The severity of HMOD was considered as single-, two-, or triple-organ damage. Results: TyG index values were higher in the hypertensive group than the normotensive group. An increased TyG index was independently associated with HMOD (OR: 1.33, p < 0.001). The TyG index exhibited gradually increasing threshold values for distinguishing patients with single-organ HMOD (> 8.8 with 77.8% sensitivity and 74.3% specificity), two-organ HMOD (> 9.1 with 77.6% sensitivity and 71.4% specificity), and triple-organ HMOD (> 9.4 with 71.5% sensitivity and 87.7% specificity). Conclusions: In newly diagnosed hypertensive patients, the TyG index exhibits significant diagnostic performance in predicting multiple-organ damage beyond the presence of HMOD. Since the detection of multiple-organ HMOD requires a multidisciplinary approach, the TyG index can serve as a simple and inexpensive screening tool.